Severe haemophilia A children on low‐dose tertiary prophylaxis showed less joint deterioration and better maintenance of functional independence than children on on‐demand treatment: A 6‐year follow‐up study. Issue 5 (22nd July 2020) - Liu, Ying; Chen, Lixia; Li, Kuixing; Shi, Mingnan; Poon, Man‐Chiu
Abstract: Background: In countries with limited resource, haemophilia patients have to choose low‐dose prophylaxis or on‐demand treatment (ODT) because of economic constraints. Whether low‐dose prophylaxis can achieve better joint function outcome than ODT over long‐term remains unclear. Aim: To investigate the long‐term effect of low‐dose tertiary prophylaxis versus ODT on joint health in severe haemophilia A children. Methods: This was a retrospective study. We enrolled and followed 34 severe haemophilia boys in China receiving on‐demand treatment (n = 18) or low‐dose prophylaxis (10‐15 IU/kg, 2‐3 times per week) for a medium‐term (6‐18 months, n = 9) or longer‐term (19‐30 months, n = 7). We evaluated their haemophilia joint health score (HJHS) 2.1 and functional independence score in haemophilia (FISH) at baseline and at their 6‐year follow‐up visits. Their annual bleeding rate (ABR) and annual joint bleeding rate (AJBR) were also recorded. Results: During the 6‐year follow‐up period, ABR and AJBR were similar between the 2 prophylaxis groups, with each of the 2 prophylaxis group rates being significantly better (lower) than the ODT group ( P  < .05). Compared to baseline values, evaluation at 6‐year follow‐up showed HJHS improvement in both prophylaxis groups, although significantly ( P  < .05) only in the longer‐term prophylaxis group. The FISH score showed insignificant change in patients in each prophylaxis cohort, compared to significant worsening ( P  < .05) in the ODT group. Conclusion: Low‐dose tertiary prophylaxis reduced ABR and AJBR of children with severe haemophilia and better maintained their functional independence by the FISH over the long term. Longer‐term prophylaxis also improved their joint health status by the HJHS.